Predictive Factors of Central-Compartment Lymph Node Metastasis for Clinical N0 Papillary Thyroid Carcinoma With Strap Muscle Invasion - Xue, Shuai; Zhang, Li; Pang, Renzhu; Wang, Peisong; Jin, Meishan; Guo, Liang; Zhou, Yuhua; Dong, Bingfei; Chen, Guang (Frontiers in Endocrinology, 2020)
Abstract Background: Papillary thyroid carcinoma (PTC) patients with anterior extrathyroidal extension (ETE) involving the strap muscle have a relatively better prognosis than those with posterior gross ETE involving the recurrent laryngeal nerve. Whether prophylactic central-compartment lymph node dissection (CLND) should be performed in PTCs with only strap muscle invasion (SMI) is still unclear. Methods: A retrospective cohort study was conducted in clinical N0 (cN0) PTC patients with SMI who underwent thyroid surgery from 2009 to 2017. A total of 152 patients were included, and predictive factors of central-compartment lymph node metastasis (CLNM) were determined. Results: Among the 281 PTCs patients with SMI, 152 (51.1%) did not clinically present with lymph node metastasis. Microscopic CLNM was identified in 77 (50.7%) cN0 PTC patients with SMI. According to the univariate and multivariate analyses, male sex and patients aged <40 years were more likely to be diagnosed with CLNM than female sex and patients aged >40 years (odds ratio [OR]=6.22 [95% confidence interval (CI), 1.43–27.10], p=0.02 vs. OR=9.94 [95% CI, 2.79–35.44], p=0.00). The CLNM positive rate of male patients aged <40 years was 87.5%, while that for female patients aged ≥55 years was 23.8%. However, risk factors associated with large-volume CLNM were not identified because of the small number of patients. Conclusions: Taken together, nearly half of PTC patients with SMI did not clinically present with lymph node metastasis. Male sex and patients aged <40 years were identified as the predictive factors of CLNM in cN0 PTCs with SMI. Hence, the results of this single-center study raise a possibility that prophylactic CLND may be more often considered for younger male PTC patients with SMI.